1973
DOI: 10.2514/3.27733
|View full text |Cite
|
Sign up to set email alerts
|

Thermal performance evaluation of REI panel gaps for Space Shuttle Orbiter.

Abstract: A series of reusable external insulation (REI) materials are being developed by the Re-Entry and Environmental Systems Division of the General Electric Company (RESD) for application to the Space Shuttle. These materials are bonded to a substrate in the form of panels resulting in numerous panel-to-panel joints. A plasmaarc ground-test facility has been used to evaluate the effects of the local heat transfer in these interface areas. Models with transverse, axial, and "tee" joints, both filled and open, have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1974
1974
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Brewer et al* 48 presented a correlation (shown in Fig. 7) for heat transfer at the bottom of transverse gaps, based on the data of Wieting, 40 Nestler, 27 and Nestler et al 18 The parameter Q g /Q A in the abscissa of Fig.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Brewer et al* 48 presented a correlation (shown in Fig. 7) for heat transfer at the bottom of transverse gaps, based on the data of Wieting, 40 Nestler, 27 and Nestler et al 18 The parameter Q g /Q A in the abscissa of Fig.…”
Section: Modelmentioning
confidence: 99%
“…[45][46][47][48] An important feature of the HH potential is the fact that its six parameters are determined by spectroscopic constants, i.e., it can be used without the need to curve fit parameters to theoretical potentials or bulk thermophysical properties as must be done for most empirical potentials. If the spectroscopic constants are known, the HH potential can be used to calculate thermophysical properties under conditions (such as high temperatures) that are experimentally inaccessible.…”
Section: Atom-ion Interaction Potentialsmentioning
confidence: 99%
“…These discontinuities at the TPS can lead to the appearance of stagnation points, hot spots, flow separation and attachment or it may induce an early boundary layer transition from a laminar to turbulent conditions [8,9]. Many experimental and numerical studies have been carried out to define and develop new materials for reusable thermal protections system that could withstand the harsh reentry environment and to accurately predict the required spacing between the TPS tiles [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Based on the available literature [19,20,24,27,29], high speed flows over cavities may be classified into four types.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental work in this area focused on ground tests (Avery, 1978, 1985; Throckmorton, 1976; Wieting, 1970; Weinstein and Avery, 1975). So far, there have been some disputes about the heat transfer mechanism in a gap (Brewer et al , 1973; Pitts and Murbach, 1982; Petley et al , 1984). The narrow geometry of a gap makes it hard to observe flow characteristics in the gap by experiments.…”
Section: Introductionmentioning
confidence: 99%